The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s12195-015-0426-3
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Progression of Epithelial Leak Caused by Overdistension

Abstract: Mechanical ventilation is necessary for treatment of the acute respiratory distress syndrome but leads to overdistension of the open regions of the lung and produces further damage. Although we know that the excessive stresses and strains disrupt the alveolar epithelium, we know little about the relationship between epithelial strain and epithelial leak. We have developed a computational model of an epithelial monolayer to simulate leak progression due to overdistension and to explain previous experimental fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The modeling results of the present study indicate that VILI develops through the stochastic appearance of new epithelial perforations roughly 50% of the time (0 < r < 0.5) and the widening of an existing hole the remaining 50% of the time (0.5 ≤ r < 1). Since a new hole must presumably be started before it can be subsequently widened, we might speculate that atelectrauma is primarily responsible for the production of new perforations through its direct damaging effects on epithelial cells [ 32 , 33 ], while volutrauma acts to enlarge existing holes via the stretch that it imposes on the alveolar tissues [ 34 ]. This theory may partially explain why recruitment maneuvers and PEEP titration were associated with increased all-cause ARDS mortality in a recent randomized trial [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The modeling results of the present study indicate that VILI develops through the stochastic appearance of new epithelial perforations roughly 50% of the time (0 < r < 0.5) and the widening of an existing hole the remaining 50% of the time (0.5 ≤ r < 1). Since a new hole must presumably be started before it can be subsequently widened, we might speculate that atelectrauma is primarily responsible for the production of new perforations through its direct damaging effects on epithelial cells [ 32 , 33 ], while volutrauma acts to enlarge existing holes via the stretch that it imposes on the alveolar tissues [ 34 ]. This theory may partially explain why recruitment maneuvers and PEEP titration were associated with increased all-cause ARDS mortality in a recent randomized trial [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Leak progression in a 45-cell (hexagon) network caused by applied stretch (i.e., Vt). After the force required to initiate the leak was reached, the leak area increased at a constant rate as the force increased further (Hamlington et al, 2016). Atelectrauma caused the initial tears, after which volutrauma expanded those tears.…”
Section: Ventilating Within the Constraints Of An Acutely Injured Lungmentioning
confidence: 99%
“…Further support for the contention that volutrauma of normal lung tissue is not a primary VILI mechanism comes from the Bates group, who showed that 4 h of mechanical ventilation in mice with high static strain was not associated with lung injury, but when it was combined with high dynamic strain, it caused VILI-induced tissue damage (Seah et al, 2011). Protti et al (2014) showed that a large dynamic strain (atelectrauma) is much more harmful to the normal lung than a large static strain (volutrauma), and when combined, the two work additively or synergistically to greatly accelerate tissue damage (Seah et al, 2011;Hamlington et al, 2016;Ruhl et al, 2019). In addition, the heterogeneous injury caused by ARDS establishes many areas of stress-focus between the open tissue and collapsed or unstable tissue and have been shown to double the stress and strain calculated for the entire lung (Cressoni et al, 2014).…”
Section: Vili Mechanisms: Heterogeneous Alveolar Instability and Collmentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, this can result in a "baby lung" scenario that results in volu-trauma to those portions of the lung that are patent, while other regions remain atelectic. A full understanding of this type of interaction would require a multiscale model that links airway and alveolar fluid-structure behaviors that incorporate physicochemical interactions (2,9,17,32,36,39).…”
mentioning
confidence: 99%